Investigation of multichannel phased array performance for fetal MR imaging on 1.5T clinical MR system - Li, Ye; Pang, Yong; Vigneron, Daniel; Glenn, Orit; Xu, Duan; Zhang, Xiaoliang (Quantitative Imaging in Medicine and Surgery, 2011)
Fetal MRI on 1.5T clinical scanner has been increasingly becoming a powerful imaging tool for studying fetal brain abnormalities in vivo. Due to limited availability of dedicated fetal phased arrays, commercial torso or cardiac phased arrays are routinely used for fetal scans, which are unable to provide optimized SNR and parallel imaging performance with a small number coil elements, and insufficient coverage and filling factor. This poses a demand for the investigation and development of dedicated and efficient radiofrequency (RF) hardware to improve fetal imaging. In this work, an investigational approach to simulate the performance of multichannel flexible phased arrays is proposed to find a better solution to fetal MR imaging. A 32 channel fetal array is presented to increase coil sensitivity, coverage and parallel imaging performance. The electromagnetic field distribution of each element of the fetal array is numerically simulated by using finite-difference time-domain (FDTD) method. The array performance, including B1 coverage, parallel reconstructed images and artifact power, is then theoretically calculated and compared with the torso array. Study results show that the proposed array is capable of increasing B1 field strength as well as sensitivity homogeneity in the entire area of uterus. This would ensure high quality imaging regardless of the location of the fetus in the uterus. In addition, the paralleling imaging performance of the proposed fetal array is validated by using artifact power comparison with torso array. These results demonstrate the feasibility of the 32 channel flexible array for fetal MR imaging at 1.5T.